Improving Students' Self-Confidence in Learning Through Action Research: Presentation Skills in Focus Improving Students' Self confidence in Learning - Mekonnen, Leul (DAS Institute, 2025)
This action research aimed to improve students' self-confidence in learning, with a specific focus on presentation skills. It was initiated and implemented by the practitioner at a Teacher College in Injibara, Amhara Region, Ethiopia. The participants were second-year regular Civic and Ethical Studies student teachers from Room 10. Out of 18 student teachers, six were purposively selected to identify the root causes of the problem. Data were collected through interviews and direct quotations, which were analyzed qualitatively using descriptive sentences, while data gathered via presentation rubrics, were analyzed using percentages. The pre-intervention findings revealed that shyness, nervousness, fear, and lack of knowledge hindered students from delivering oral presentations confidently in front of an audience. Based on these findings, intervention strategies were designed to address these challenges. After implementing these strategies over four months, the project proved successful in enhancing students’ oral presentation skills and reducing nervousness and fear.